(untitled) (Dhaka University Journal of Biological Sciences, 2018)
The effects of number of bystander, time pressure and gender on showing altruistic behavior was investigated. This covered three hypotheses that: (i) individual would exhibit more altruistic behavior to the victim when they are alone in a situation than being in a group, (ii) time pressure would inhibit altruistic behavior and (iii) there would be no differences between males and females in case of showing altruistic behavior. A total of 40 individuals (20 males and 20 females) and another 20 groups of strangers were the sample of this study and three field experiments were done to examine the hypotheses. Findings revealed that increasing number of bystanders decreased the probability of showing altruistic behavior, under time pressure people less likely to help others and no significant difference was found between males and females in showing altruistic behaviour. The result of the present study can provide a greater understanding of why people fail to do what is morally expected and thus lead to a greater tolerance and understanding of others. Dhaka Univ. J. Biol. Sci. 27(1): 1-7, 2018 (January)